2013
DOI: 10.1111/clr.12115
|View full text |Cite
|
Sign up to set email alerts
|

Peri‐implant bone formation of non‐thermal atmospheric pressure plasma–treated zirconia implants with different surface roughness in rabbit tibiae

Abstract: The He plasma treatments on PIM zirconia implants made the surface more hydrophilic and enhanced the osseointegration of the implants without changing the micro-topography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 37 publications
3
31
0
6
Order By: Relevance
“…Before plasma treatment, the smooth sample presented longitudinal, parallel grooves while the rough sample resulted in a highly irregular structure. Not surprisingly, the surface morphology was does not altered by oxygen plasma treatment, in agreement with previous studies [11,14], possibly because the used power of plasma was not enough to change the morphology of hard ZrO 2 surface. The roughness of the TZP samples after exposure to the plasma was also investigated.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Before plasma treatment, the smooth sample presented longitudinal, parallel grooves while the rough sample resulted in a highly irregular structure. Not surprisingly, the surface morphology was does not altered by oxygen plasma treatment, in agreement with previous studies [11,14], possibly because the used power of plasma was not enough to change the morphology of hard ZrO 2 surface. The roughness of the TZP samples after exposure to the plasma was also investigated.…”
Section: Resultssupporting
confidence: 91%
“…Yoshinari and co-workers found that blast/acid etching, oxygen plasma treatment and ultraviolet light irradiation greatly increased the surface wettability of the zirconia disks, resulting in superhydrophilicity [13]. Shon et al indicated that helium plasma treatments on powder-injection molded zirconia implants made the surface more hydrophilic and enhanced the osseointegration of the implants in a rabbit tibiae mode without changing the microtopography [14]. …”
Section: Introductionmentioning
confidence: 99%
“…Machined and surface-modified zirconia implants were considered in 3 studies [14, 18, 21]. PIM-treated and untreated zirconia implants were installed in 4 studies [15, 2729]. Five studies compared RT values of zirconia with modified zirconia implants [14, 15, 2729].…”
Section: Resultsmentioning
confidence: 99%
“…They also demostrated the increase in hydrophilicity and enhanced osseointegration in in vitro as well as in vivo experiments [28,30]. …”
Section: Surface Treatmentmentioning
confidence: 99%